Electrocardiographic Changes at the Early Stage of Status Epilepticus: First Insights From the ICTAL Registry*. Issue 3 (19th December 2022) - Chinardet, Paul; Gilles, Floriane; Cochet, Helene; Chelly, Jonathan; Quenot, Jean-Pierre; Jacq, Gwenaelle; Soulier, Pauline; Lesieur, Olivier; Beuret, Pascal; Holleville, Mathilde; Bruel, Cedric; Bailly, Pierre; et al.
Abstract : Objectives: To describe early electrocardiogram (ECG) abnormalities after status epilepticus (SE) and evaluate their association with 90-day neurological outcomes. Design: Retrospective analysis of a multicenter, national prospective registry between February 2018 and June 2020. Setting: Sixteen ICUs in France, IctalGroup Research Network. Patients: Adults with available ECG performed less than or equal to 24 hours after the onset of SE and less than or equal to 12 hours after its resolution. Intervention: Double-blinded review of all ECGs was performed by two independent cardiologists. ECGs were categorized as normal/abnormal and then with minor/major early ECG abnormalities according to the Novacode ECG Classification system. Measurements and Main Results: Among 155 critically ill patients with SE, early ECG abnormalities were encountered in 145 (93.5%), categorized as major in 91 of 145 (62.8%). In addition to sinus tachycardia, the main abnormalities were in the ST segment (elevation [16.6%] or depression [17.9%]) or negative T waves (42.1%). Major early ECG abnormalities were significantly associated with respiratory distress and sinus tachycardia at the scene and hyperlactatemia at ICU admission. By multivariable analysis, three variables were significantly associated with 90-day poor outcome: age, preexisting ultimately fatal comorbidity, and cerebral insult as the cause of SE. Early major ECG abnormalities were not independently associated with 90-day functional outcome. Conclusions: In our study, early ECG abnormalities in the acute phase of SE were frequent, often unrecognized and were associated with clinical and biological stigma of hypoxemia. Although they were not independently associated with 90-day functional outcome, ECG changes at the early stage of SE should be systematically evaluated. TRIAL REGISTRATION: https://clinicaltrials.gov/ct2/show/NCT03457831 .